2013
DOI: 10.1111/j.1600-6143.2012.04341.x
|View full text |Cite
|
Sign up to set email alerts
|

Belatacept and Sirolimus Prolong Nonhuman Primate Islet Allograft Survival: Adverse Consequences of Concomitant Alefacept Therapy

Abstract: Calcineurin inhibitors (CNI) and steroids are known to promote insulin resistance, and their avoidance after islet transplantation is preferred from a metabolic standpoint. Belatacept, a B7-specific mediator of costimulation blockade (CoB), is clinically indicated as a CNI alternative in renal transplantation, and we have endeavored to develop a clinically translatable, belatacept-based regimen that could obviate the need for both CNIs and steroids. Based on the known synergy between CoB and mTOR inhibition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 21 publications
(26 reference statements)
2
30
0
Order By: Relevance
“…Studies in murine models have showed synergy between costimulation blockade and mTOR inhibitors (17). Studies in nonhuman primates have demonstrated that the combination of belatacept and sirolimus prolong renal and islet allografts survival (18,19), and we have demonstrated a therapeutic effect in NHP VCAs (data not shown). Clinically, Phase III trials have shown supremacy of belatacept in the conservation of renal function and other adverse events compared to CNIs (4).…”
Section: Discussionmentioning
confidence: 85%
“…Studies in murine models have showed synergy between costimulation blockade and mTOR inhibitors (17). Studies in nonhuman primates have demonstrated that the combination of belatacept and sirolimus prolong renal and islet allografts survival (18,19), and we have demonstrated a therapeutic effect in NHP VCAs (data not shown). Clinically, Phase III trials have shown supremacy of belatacept in the conservation of renal function and other adverse events compared to CNIs (4).…”
Section: Discussionmentioning
confidence: 85%
“…Strategies that target integrins on T cells, for example antibodies to LFA-1 or VLA-4, have proven effective but unsafe in the clinic because they interfere with the immune surveillance functions of memory T cells leading to the reactivation of latent infections (21, 22). Targeting molecules downstream of the TCR on the other hand could potentially be more specific, singling out only those effector or memory cells that are engaging Ag at the time.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR)-based assays for rhesus macaque homologs of CMV and EBV, rhCMV (Yue and Barry 2008) and LCV (Rao et al 2000;Rivailler et al 2004), respectively, are available for monitoring. Regular monitoring of transplanted animals can provide insight into the extent of immunosuppression, and perhaps, indicate when a regimen may excessively compromise protective immunity (Lo et al 2013;Lowe et al 2013). …”
Section: Perioperative Carementioning
confidence: 99%
“…Persistent interest in this pathway led to the development of belatacept, which differs from the base CTLA4-Ig protein by only two amino acids, but shows significantly higher inhibition of CD28 signaling (Larsen et al 2005). Belatacept was shown to be effective as maintenance therapy in primate models of islet and renal transplantation (Cardona et al 2006;Lo et al 2013;Lowe et al 2013), and subsequent clinical trials led to its successful translation to human use.…”
Section: Costimulation Blockadementioning
confidence: 99%
See 1 more Smart Citation